2018
DOI: 10.1039/c8fo01227j
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry, combined with probiotics, alleviates non-alcoholic fatty liver diseaseviaIL-22-mediated JAK1/STAT3/BAX signaling

Abstract: Blueberry, combined with probiotics, improves non-alcoholic fatty liver disease bothin vivoandin vitroby IL-22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…The main composition of blueberry juice was detected as described in the previous study. 15 As shown in our previous study, 16 the anthocyanin concentration in blueberry juice was 0.98 ± 0.07 mg mL −1 . Dry probiotic tablets mixed with the probiotic species of Bifidobacterium infantis, Bifidobacterium animalis, and Lactobacillus acidophilus were obtained from the China General Microbiological Culture Collection Center (Beijing, China).…”
Section: Preparation Of Bpmentioning
confidence: 60%
“…The main composition of blueberry juice was detected as described in the previous study. 15 As shown in our previous study, 16 the anthocyanin concentration in blueberry juice was 0.98 ± 0.07 mg mL −1 . Dry probiotic tablets mixed with the probiotic species of Bifidobacterium infantis, Bifidobacterium animalis, and Lactobacillus acidophilus were obtained from the China General Microbiological Culture Collection Center (Beijing, China).…”
Section: Preparation Of Bpmentioning
confidence: 60%
“…Contrarily, the anti-inflammatory effect was less pronounced in some animal studies and human [21, 36, 37]. New reports indicated that blueberry extracts can significantly inhibit inflammatory and apoptosis via activation of JAK1/STAT3 signaling [38], PPARγ activity [39] or survival PI3K/Akt and MAPK/ERK pathways [40].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of IL-22 to IL-22R activates downstream signal transduction (Figure 1) (39). IL-22 transmits phosphorylation signals downstream through Janus kinase (JAK) 1 and tyrosine kinase (TYK) 2, including the mitogen-activated protein kinase (MAPK) pathway (p38 kinase, ERK1/2, MEK1/2 and JNK), STAT3, STAT1 and STAT5 (39)(40)(41). Similar to other members of the IL-10 family, IL-22 phosphorylates STAT3 mainly at Ser727 and Tyr705 (23,42,43).…”
Section: Characteristics Of Th22 Cellsmentioning
confidence: 99%